THE EFFECT OF THE DIGITAL REVOLUTION ON GLOBAL MARKETING IN ERA 4.0 AND CONSUMER BEHAVIOR - Divia Zulianti; Sri Kartika Dewi; Vanya Nurul Izza; Suhairi (Journal of Social Research, 2022)
In today's sophisticated era, the digital revolution continues to develop. Today, the world's industry and manufacturing has faced a revolution that has changed all kinds of existing forms of industry. Especially in the fourth era or the digital revolution. Era 4.0 is marked by the emergence of various changes that occur in technology that have an impact on various fields, and one of them is the marketing aspect. Marketing has now shifted from the traditional marketing concept to Global Marketing, where today's trade has reached a matter of seconds because all transactions are carried out online with the help of the internet and can spread widely anywhere, both domestically and abroad. The digital revolution has also changed consumer behavior towards marketing. This change in consumer behavior can also be seen from the way they search for, pay for, use and dispose of purchased goods after consumption. Consumer habits in consuming media have also changed drastically, and this has prompted marketers to create strategies and innovate to find more effective alternative channels to attract consumers